Pengaruh Demokrasi terhadap Pertumbuhan Ekonomi Daerah di Indonesia - Utomo, Jayanti Kusumaningrum; Soetjipto, Widyono (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study observes that previous research on the relationship between democracy and economic growth has produced ambiguous outcomes. The aim of this paper is to estimate the relationship between democracy and regional economic growth in Indonesia. Using a fixed effects model with 374 provincial-level observations, the results indicate a statistically significant and positive relationship between democracy and regional economic growth in Indonesia.